Antecedents of the intention to buy animal welfare certified products: A study with brazilian consumers - de Castro Júnior, Sérgio Luís; Spers, Eduardo Eugênio; da Silva, Hermes Moretti Ribeiro [UNESP]; da Silva, Iran José Oliveira (Springer Nature, 2025)
Animal welfare, often regarded as a singular and generic factor, necessitates explanatory models that reflect its multidimensional nature. This study addresses this complexity by investigating the purchasing behavior of consumers in developing countries, focusing on animal welfare-certified foods. To achieve this goal, a conceptual analytical model was developed, grounded in an extensive literature review and expert consultations. The model positions beliefs about animal welfare as the central component, with empathy for animals and knowledge of the production sector as antecedents. It also identifies beliefs about certified products, engagement, and perceived quality attributes as consequences. The methodology involved an online survey of 707 Brazilian consumers to test eight hypotheses derived from the model using structural equation modeling. The findings confirmed all hypotheses at a significance level of p ≤ 0.05, underscoring the cognitive, affective, and educational bases of consumer beliefs about animal welfare. These beliefs were shown to positively influence engagement with, and perceived quality attributes of, certified products, ultimately shaping purchase intentions. However, a negative relationship between beliefs about animal welfare and beliefs about certified products suggests skepticism among Brazilian consumers regarding certification systems. This study contributes to the literature by presenting a multidimensional model that offers both theoretical insights and practical implications for marketing strategies and certification systems, particularly in developing country contexts. This novel approach lays a foundation for future cross-cultural validations and product-specific investigations.
Keywords: Animal welfare products; Consumer behavior; Food-purchasing behavior; Marketing; Structural equation models